The frozen conflict in Western Sahara and the forgotten question of Sahrawi - Marsili, M. (Review of Human Rights, 2024)
Western Sahara’s “frozen conflict” is one of the major and forgotten issues that, so far, the international community was not able to settle. This article aims to shed light over the historical events and the political responsibilities that led to a long stalemate over the Sahrawi question. The paper retraces the historical roots of the claims over the disputed territory by the Polisario Front, as the representative of the Sahrawi people, over the disputed territory, and analyzes their foundations under the light of international law.